National and international animal welfare auditing standards - Aguirian, Allen Jimena M.,; Garcia, Arlene,; Johnson, Anna K., (Life Sciences E-Books Online, Collection 2026., 2026)
Animal welfare is an evolving science, driven by growing consumer demand for responsible farming practices. This groundbreaking book focuses on the background, development, implementation, and resources needed for effective farm animal welfare auditing. It offers a comprehensive introduction to animal welfare science, highlights best practices for developing standards, and reviews national and international standards, audit tools, and certification programs. It provides the foundation needed to understand, design, and implement auditing programs. Serving as both a guide and a resource, this book supports academics, industry professionals, and stakeholders in promoting welfare practices that meet market expectations and improve animal welfare outcomes.